Glomerular disease associated with cancer: a case series of paraneoplastic nephrotic syndrome - Hu, Mengsi; Ma, Qiqi; Wang, Liguang; Zhang, Tingwei; Lin, Jiangong; Yang, Xiaowei; Lv, Zhimei; Wang, Rong (Frontiers in Medicine, 2025)
The association between glomerular diseases and malignancies has been recognized since the 1920s. A diverse spectrum of glomerular lesions can occur in various neoplasms, including both hematologic malignancies and solid tumors. This study presents a case series of paraneoplastic nephrotic syndrome (PNS) associated with three solid tumors: ovarian cancer, pancreatic neuroendocrine tumor (NET), and bladder cancer. The occurrence of PNS is rarely reported in association with these malignancies. Notably, all patients achieved complete or partial remission without receiving corticosteroids or immunosuppressant therapy. These observations accentuate the critical role of malignancy in the pathogenesis of glomerulopathy and underscore the therapeutic primacy of oncological control in such patients.